1986
DOI: 10.1017/s0317167100037082
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Neurotoxicity — Potential Role in the Pathogenesis of Neurofibrillary Tangle Formation

Abstract: Abstract:Alzheimer's disease is a progressive neurodegenerative disease characterized neuropathologically by the development of large numbers of neurofibrillary tangles in certain neuronal populations of affected brains. This paper presents a review of the available evidence which suggests that aluminum is associated with Alzheimer's disease and specifically with the development of the neurofibrillary tangle. Aluminum salts innoculated into experimental animals produce neurofilamentous lesions which are simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…To eliminate the likelihood that the same cell would be counted twice, slices for each histological experiment were drawn from only one well of the collection dish to ensure that sections were at least 250 μm apart. Regions of interest for cell counts were defined using landmarks and reference points from mouse spinal cord and brain stereotaxic atlases [39,40]. In the spinal cord, only cells which were anterior to the central canal and deep apex where the grey and white matters meet were considered as part of the ventral horns; conversely, only cells which were posterior to the central canal and the posterior deep apex were considered as part of the dorsal horns.…”
Section: Methodsmentioning
confidence: 99%
“…To eliminate the likelihood that the same cell would be counted twice, slices for each histological experiment were drawn from only one well of the collection dish to ensure that sections were at least 250 μm apart. Regions of interest for cell counts were defined using landmarks and reference points from mouse spinal cord and brain stereotaxic atlases [39,40]. In the spinal cord, only cells which were anterior to the central canal and deep apex where the grey and white matters meet were considered as part of the ventral horns; conversely, only cells which were posterior to the central canal and the posterior deep apex were considered as part of the dorsal horns.…”
Section: Methodsmentioning
confidence: 99%
“…This Al overload resulted in a fatal neurological syndrome (dialysis dementia) and a devastating metabolic bone disease known as dialysis osteodystrophy (reviewed by Mach et al, 1988). Al has been linked to neurotoxicity (Levesque et al, 2000;Perl and Pendlebury, 1986;Roll et al, 1989;SuarezFernandez et al, 1999;Troncoso et al, 1985;Tsubouchi et al, 2001) and implicated as a possible causative or contributing factor in neurodegenerative disorders particularly Alzheimer's disease (AD), although the exact mechanism by which it acts is far from clear (Crapper McLachlan, 1986;Shin et al, 1995;Strong, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have either reported [61], or not reported [109], Al in association with the cores of classic Ab deposits, but it is not clear whether this type of SP is especially frequent in AD [18]. Al has also been detected in pyramidal neurons containing NFT [142,143]. It has been suggested that Al can bind to DNA and affect processing of cytoskeletal proteins resulting in the formation of NFT.…”
Section: Aluminiummentioning
confidence: 99%